A theoretical explanation of defective verbs in the Spanish language - O'Neill, P (2010)
This study examines the theoretical reasons which have been deduced up to the present to highlight defective verbs in the Spanish language. We hold that the current proposals are not capable of attesting to the descriptive facts. We place special emphasis on the fact that defective verb patterns adjust to allomorphic alternation and propose that such allomorphs cannot be derived phonologically, but are, on the contrary, of a morphological nature. Consequently, in our proposal, the patterns of allomorphs correspond with purely morphological structures, or morphemes (Aronoff 1994, Maiden 2004) and it is obligatory that speakers memorise a method for such structures. We maintain that defective verbs of a non-semantic type in the Spanish language are due to the fact that the conjugation of group three verbs, apart from containing a general verbal root, also store a particular root (or roots) for different morphemes; defects therefore arise when verbs lack at least one of these roots. We present evidence of diachronic, experimental and computational studies to support this hypothesis.